2016
DOI: 10.1037/a0040343
|View full text |Cite
|
Sign up to set email alerts
|

Ecocultural patterns of family engagement among low-income Latino families of preschool children.

Abstract: For the five million low-income Latino children in the United States who are disproportionately impacted by the numerous risk factors associated with poverty, it is essential to identify proximal protective factors that mitigate these risks and bolster the academic and social skills that are foundational to a successful transition into formal schooling. Using ecocultural theory as a lens to guide this work, the present study: (1) described patterns of culture-contextualized family engagement among a low-income… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 67 publications
0
30
0
1
Order By: Relevance
“…The present study builds upon research that explores these contributions by examining the ways that parents support their children's reading skills, motivation, and habits through both everyday, authentic reading routines and common school-based practices. Although literacy is far broader than skills implicated while reading books (Perry, 2012), the present study's emphasis on parents' support of reading print, and books specifically, builds upon a research base that suggests that parents 4 from low-SES communities place a high value on developing reading skills promoted in school (Compton-Lilly et al, 2016;Hammer et al, 2005;Jarrett et al, 2015;McWayne et al, 2016).…”
Section: Study Contributionsmentioning
confidence: 96%
“…The present study builds upon research that explores these contributions by examining the ways that parents support their children's reading skills, motivation, and habits through both everyday, authentic reading routines and common school-based practices. Although literacy is far broader than skills implicated while reading books (Perry, 2012), the present study's emphasis on parents' support of reading print, and books specifically, builds upon a research base that suggests that parents 4 from low-SES communities place a high value on developing reading skills promoted in school (Compton-Lilly et al, 2016;Hammer et al, 2005;Jarrett et al, 2015;McWayne et al, 2016).…”
Section: Study Contributionsmentioning
confidence: 96%
“…Research based on Weisner’s ecocultural theory has also proven the shaping of culture in everyday routines (Newland et al, 2013; Plowan, Stevenson, Stephen, & McPake, 2011). McWayne et al (2016) explore the “niche profiles” of families engagement practices in a group of low-income Spanish- and English-speaking Latino families of preschool children. They found that there is heterogeneity in the pattern of family engagement practices among the families and demographic factors were good predictors of the pattern on the language group and have a relationship with children’s social and language skills.…”
Section: Empirical Studies That Support the Cultural Microsystems Parmentioning
confidence: 99%
“…McWayne et al (2016) used the ecocultural perspective to investigate the distinct patterns of engagement among 650 Spanish and English self-identified Latinos primary caregivers of Head Start children with low income and 38 teachers and to examine the relation between the patterns, family demographic factors, and children’s language and social skills. The findings suggested that providers of care who reported low engagement had less education than those who reported average engagement.…”
Section: Empirical Studies That Support the Cultural Microsystems Parmentioning
confidence: 99%
“…If parents’ engagement is predominantly determined by available time and resources, for example, rather than their trust in or comfort with their child’s school, racial/ethnic match is not likely to affect parental involvement. However, if parents are engaged with their child’s education in ways typically not valued by schools, it is possible that working with a teacher who understands a parent’s cultural space and values their contributions (Gaitan, 2012; McWayne et al, 2016) may generate further involvement with Head Start. Perhaps unsurprisingly, the literature linking match to involvement is mixed.…”
Section: Benefits Of Teacher-child Racial/ethnic Match For Children Amentioning
confidence: 99%